Intensification strategies of primary teachers discourse about sexual and functional diversity - Fernández Fernández, Daniel (2019)
The present paper analyses the intensification strategies used by the primary school teachers discourse about sexual and functional diversity. Intensification strategies constitutes a pragmalinguistic mechanism through which the speaker stablish a certain level of proximity in the frame of a particular communicative interaction. Methodologically, the article proposes a qualitative approach based on three different processes: the identification and description of intensification resources in the enunciative setting and the elaboration of discursive inferences throughout an analytical theoretical articulation. The results of the research process show that the tendency of trying to achieve a mutual agreement with the interlocutor, represents a mechanism to make the elocutions believable and, in the same direction, a way to protect the self-image (front) that, concomitantly, reflects the difficulties that the teachers have approaching sexual and functional diversity